Abiotic and biotic controls of phytoplankton biomass dynamics in a freshwater tributary, estuary, and large lake ecosystem: Sandusky Bay (Lake Erie) chemostat. Issue 4 (2nd October 2017) - Conroy, Joseph D.; Kane, Douglas D.; Quinlan, Erin L.; Edwards, William J.; Culver, David A.
Abstract: The classic view of tributary–lake interactions solely considers tributaries as sources of nutrients for phytoplankton growing offshore. We tested how river input of phytoplankton affected dynamics in a lacustrine estuary and how these phytoplankters could, upon discharge, affect offshore phytoplankton dynamics. In addition, we explored whether phytoplankton biomass was controlled by bottom-up abiotic factors (stream flow, temperature, light attenuation, and nutrient concentrations) or top-down biotic factors (zooplankton herbivory) and the role the lacustrine estuary played in modifying the quality of the water discharged into the lake. We tested these possibilities using field sampling over 2 years in the Sandusky River, Sandusky Bay, and the Sandusky subbasin of Lake Erie in conjunction with river flow and nutrient monitoring and multivariate statistical analysis of the relationships among the various datasets. Nutrient loading to the estuary corresponded with watershed input; nutrients were used within the estuary, decreasing nutrient loads to the lake. Phytoplankton biomass, however, was extremely high in the estuary and was much higher at the bay–subbasin interface than offshore, indicating that the estuary likely discharges phytoplankton to the nearshore area, not offshore. An information-theoretic analysis of 15 candidate models showed that phytoplankton biomass was best predicted by the ratio of total inorganic nitrogen to total phosphorus, indicating bottom-up control. The lacustrine estuary therefore functions as a chemostat, using incoming nutrients to grow large amounts of phytoplankton. Our results indicate that the classic model of tributary–bay interactions needs revision to include phytoplankton load and its subsequent effects within the lake.